2014
DOI: 10.1111/sdi.12337
|View full text |Cite
|
Sign up to set email alerts
|

Low Dialysate Potassium Concentration: An Overrated Risk Factor for Cardiac Arrhythmia?

Abstract: Serum potassium concentrations rise with dietary potassium intake between dialysis sessions and are often at hyperkalemic levels by the next session. Conversely, potassium concentrations fall during each hemodialysis, and sometimes reach hypokalemic levels by the end. Low potassium dialysate, which rapidly decreases serum potassium and often brings it to hypokalemic levels, is almost universally considered a risk factor for life-threatening arrhythmias. While there is little doubt about the threat of lethal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Both low blood potassium levels (hypokalemia) and high blood potassium levels (hyperkalemia) can lead to abnormal heart rhythms. 45 We observed colocalization of the GWAS signal for UACR and UK/UCr in the GATM locus with mQTL signals. The GATM locus is not novel in terms of association with renal function, as previous studies have shown its association with CKD and reduced glomerular filtration rate.…”
Section: Novel Biologymentioning
confidence: 70%
“…Both low blood potassium levels (hypokalemia) and high blood potassium levels (hyperkalemia) can lead to abnormal heart rhythms. 45 We observed colocalization of the GWAS signal for UACR and UK/UCr in the GATM locus with mQTL signals. The GATM locus is not novel in terms of association with renal function, as previous studies have shown its association with CKD and reduced glomerular filtration rate.…”
Section: Novel Biologymentioning
confidence: 70%
“…The effects of dialysate potassium concentration are less clear. Although interventions that reduce the rapidity of potassium changes during hemodialysis have been shown to reduce the risk of premature ventricular complexes (33), others have questioned the broader clinical effect of serum and dialysate potassium gradients (34). Finally, magnesium appears to play an important role in maintaining myocardial electrical stability and regulating vascular smooth muscle tone.…”
Section: Maintenance Of Cardiac Outputmentioning
confidence: 99%
“…Low potassium can be caused by low dietary potassium intake, malnutrition, chronic diarrhea, or the use of prescription drugs [77]. Furthermore, with the use of a low potassium dialysate, K þ is removed mainly from the extracellular space and only slightly from the intracellular space; thus, the extracellular potassium level decreases too abruptly, and the intracellular/extracellular potassium ratio increases rapidly [78].…”
Section: Electrolyte Disorder and Hemodialysismentioning
confidence: 99%